THE SELLERS ’ KNOWLEDGE OF THE MARKETING EXTENSION OF THE LOCAL HONEY SHOPPING FUNCTION AND ITS RELATIONSHIP WITH SOCIAL VARIABLES IN SULAIMANIYAH GOVERNORATE - Abdulrahman, shanya; Dara A. Salih (University of Thi-Qar Journal of agricultural research, 2025)
The research aimed to determine the level of sellers’ knowledge of the marketing extension of the local honey marketing function and its relationship to some variables. This research was conducted in Sulaymaniyah governorate on a simple random sample of 313 researchers, representing 30% of the research community of 939 researchers. The data was collected by personal interview through a questionnaire form prepared for this purpose, and after testing and confirming its suitability for data collection, the data were collected, then processed and analyzed by SPSS Version22 Software. The results found that the level of knowledge of the respondents in the marketing extension of local honey in general was average, tending to rise, and the percentage of respondents in the middle and high categories was 71.57%. Additionally, the results showed that there is a significant correlation between the level of knowledge of the respondents in the marketing extension and variables: age, educational level and use of information source of marketing, while there is no correlation between the level of knowledge of the respondents in the marketing extension and participation in social organization variable. The researcher recommends that the development of specialized training and extension programs designed for different ages and education levels for honey sellers by the Ministry of Agriculture to maximize learning outcomes for honey sellers.